2020
DOI: 10.1002/adom.201902092
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Förster Resonance Energy Transfer in Close‐Packed Quantum‐Dot Thin Film: Toward Efficient Quantum‐Dot Light‐Emitting Diodes with External Quantum Efficiency over 21.6%

Abstract: the presence of Förster resonance energy transfer (FRET) among the close-packed QDs, [19][20][21][22][23][24] which thus limits the efficiency of QD LEDs (QLEDs). FRET is a nonradiative energy transfer process, in which the energy is down-transferred from a fluorescent donor to an acceptor via the dipoledipole coupling if the distance between donor and acceptor is smaller than the transfer radius (typically <10 nm). [24][25][26] In close-packed QD solids, interdot FRET can be very efficient due to the small di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
3
34
2
Order By: Relevance
“…The PL intensity sharply declined with further increase of the QDs ratios to 15% and 20%, owing to the exciton quenching induced by the accumulation and aggregation of the massive QDs in the QPFs. [34] To further study the exciton recombination processes, the time-resolved PL (TRPL) spectra of the QPFs have been measured (Figure 3b). The decay dynamics can be well fitted by three-exponential curves and the extracted parameters are collected and listed in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The PL intensity sharply declined with further increase of the QDs ratios to 15% and 20%, owing to the exciton quenching induced by the accumulation and aggregation of the massive QDs in the QPFs. [34] To further study the exciton recombination processes, the time-resolved PL (TRPL) spectra of the QPFs have been measured (Figure 3b). The decay dynamics can be well fitted by three-exponential curves and the extracted parameters are collected and listed in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the FRET from blue to green and red QDs, which is well consistent with the PLQY measurement, that is, when the mixed QDs formed a QD layer, PLQY of blue QDs significantly decreased as FRET increased due to the reduced dot-to-dot distance which was discussed in Figure 1. [21][22][23][24][25][26]28] However, the severe imbalance of the RGB ratio leads to degradation of white QLED performance because a turn-on voltage of a QLED would increase due to the high ratio of blue QDs with the larger bandgap as evidenced by the turn-on voltage of warm and daylight white QLEDs in Table 1. Therefore, smaller amount of blue QDs is desirable with the same CCT value.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, FRET is probably the primary cause for the difference. A recent work [38] demonstrated that the FRET among red-QDs can be suppressed by blue-QDs as spacers. This implies that FTIR will be suppressed to different degrees for different color quantum dots depending on the ratio of RGB QDs.…”
Section: B Microcavity With Mixed Rgb Qdmentioning
confidence: 99%